Rancang Bangun Mesin Irat Bambu Dengan Penggerak Motor Listrik 1 HP - (Jurusan Teknik Mesin Politeknik Negeri Semarang), Alan Dirganata, Eko Armanto, Suyadi (Teknis, 2016)
Bamboo is a plant species of grasses with a cavity and a segment in the trunk. Bamboo has many types. In this era of bamboo has economic value and beneficial if used properly. One way is to become of utilizing bamboo handicrafts. Bamboo craft is a craft popular among the people of Indonesia, ranging from woven bamboo crafts, woven wall, Udung misstatement, tissue boxes and skewers. Irat bamboo is a tool that has a working principle attenuate or splitting bamboo section in accordance with a predetermined size. This tool is used to produce various kinds of craft in bulk with the results of the same product in a relatively short time. The purpose of this design tool is to cut the bamboo in large quantities in a short time. The method used to design and make bamboo irat engine with an electric motor with a power capacity of 600 incision 1HP per hour. Motor rotation speed listrikhasil incision bamboo with bamboo irat engine with an electric motor capable of producing bamboo incision to the size of Â± 5m.Keywords: Design, Engineering Irat, Bamboo, Electric Motors